Leveraging the COVID-19 crisis in making work-from-home a mainstream practice in the oil and gas industry - Dewi, Indira; Adiarsi, Gracia Rachmi (Jurnal Komunikasi Profesional, 2020)
During the COVID-19 crisis, the oil and gas industry is among industries that face challenges in selling their products and struggling to manage their cash flow. The pressure to improve financial discipline within the oil and gas industry started even before the COVID-19 crisis. This paper validates the feasibility of adopting work-from-home (WFH) as a permanent practice for oil and gas companies in Indonesia and how it will help to reduce costs, enhance employee productivity, and improve their organizational agility. The survey was conducted two weeks after the start of the forced WFH â€œexperiment.â€Â One hundred nine executives from various oil and gas companies in Indonesia took part in the survey. The result of this study resulted in most of the large and established companies in Indonesia, in particular, the oil and gas companies, being slow in adopting this practice. The COVID-19 crisis could be the turning point for wider and lasting adoption of WFH in the oil and gas industry. The survey results validate that business can still run even when their employees are working from home.Â Also, the survey results showed that a shift of opinion toward accepting WFH as the new normal exists. The survey indicates that many companies have crossed psychological and mental blocks and are receptive to the idea of making WFH part of normal HR practices.Keywords:Â WFH;Â Management;Â Sustainability;Â Oil andÂ GasÂ Industry.